Multiple sclerosis lesions exhibit sex-specific steroid changes - Sabina Luchetti; Matthew R.J. Mason; Philippe Liere; Antoine Pianos; Sara Cossu; Marloes Hofstee; Arja Sluiter; Adelia; Jackelien van Scheppingen; Eleonora Aronica; Michael Schumacher; Inge Huitinga (Neurobiology of Disease, 2025)
Sex differences in disease susceptibility and progression in multiple sclerosis (MS) indicate hormonal influences. We previously found sex differences in steroidogenic enzyme expression in mixed active/inactive (mixed) and inactive lesions, suggesting increased synthesis and signalling of progesterone in females and of estradiol (E2) in males. Here we measured steroid levels in mixed and inactive MS lesions (14 males, 16 females) and control donor white matter (10 males, 10 females) by gas chromatography–mass spectrometry (GC/MS). In mixed and inactive lesions, we found a female-specific increase in the production of the neuroactive steroid allopregnanolone, and a reduction in testosterone metabolites and the precursor androgen dehydroepiandrosterone (DHEA). In males, however, most steroids remained unchanged, although the weakly neuroactive 5α-DHDOC was increased. No significant differences were found in steroid levels in remyelinating MS lesions (6 males, 6 females) and control donor white matter (8 males, 7 females). However, higher gene expression of steroid receptors and of the steroidogenic enzyme AKR1C3 persisted in these remyelinated lesions in females. In vitro, we found that E2, and to a lesser degree progesterone and testosterone, had mostly beneficial effects on cytokine expression in primary microglia isolated from MS donors but not from controls; and on neuroprotective gene (APOE, BDNF, GLT1, IGF1, LIF) expression in human fetal astrocytes, but only under inflammatory conditions. Sex-specific changes in the levels of steroids, their metabolizing enzymes, their receptors, and the actions of steroids on glial neuroinflammatory responses may contribute to the sex differences in MS disease progression and lesion resolution.